2022
DOI: 10.1017/flo.2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing surface-gap effects on boundary-layer transition dominated by Tollmien–Schlichting instability

Abstract: Effects of gaps (rectangular surface cavities) on boundary-layer transition are investigated using a combination of linear stability theory and experiments, for boundary layers where the smooth-surface transition results from Tollmien–Schlichting (TS) instability. Results are presented for a wide range of gap characteristics, with the associated transition locations ranging from the smooth-surface location all the way forward to the gap location. The transition movement is well described by a variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…In the present experimental campaign, both classic gaps and gaps with uneven sides, referred to as steps-and-gaps or S&G, were tested and compared to the Olive and Blanchard criteria for critical gaps. Although determining whether or not classic gaps were critical could not be ascertained due to some limitations in the wing model, the ∆N values based on the subcritical gaps showed relatively good agreement with the ∆N model for gaps proposed by Crouch et al (2022).…”
Section: Gaps and Steps-and-gapsmentioning
confidence: 92%
See 3 more Smart Citations
“…In the present experimental campaign, both classic gaps and gaps with uneven sides, referred to as steps-and-gaps or S&G, were tested and compared to the Olive and Blanchard criteria for critical gaps. Although determining whether or not classic gaps were critical could not be ascertained due to some limitations in the wing model, the ∆N values based on the subcritical gaps showed relatively good agreement with the ∆N model for gaps proposed by Crouch et al (2022).…”
Section: Gaps and Steps-and-gapsmentioning
confidence: 92%
“…The influence of subcritical defects is then analysed. This proposed by Crouch et al (2022) and the BFS ∆N model from Crouch et al (2006).…”
Section: Gaps and Steps-and-gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have looked for empirical correlations linking the type of defect and its geometrical characteristics to the shift. Wind tunnel experiments were conducted by Crouch, Kosorygin, Sutanto, and Miller (2022) on gaps and by Wang and Gaster (2005) on BFSs. These studies showed that the corresponded to for the gaps and for the BFSs, where and denote the step height and step width, respectively, made dimensionless with the boundary layer displacement thickness for a Blasius boundary layer at the defect location .…”
Section: Introductionmentioning
confidence: 99%